IMPACT OF EMBEDDED CLS ON EYE TRACKING REPLICATION - Nuris Dwi Setiawan; Bagus Sudirman; Sigit Umar Anggono (University of Science and Computer Technology, 2022)
Using different programming languages when software advancement is a familiar method in current software advancement. Nevertheless, using various languages that can hinder developer capacity is not widely known. This research simulated an unplanned controlled study examining the adoption of various languages in the situation of a directory programming task. Participants in this study were given programming tasks written in Java and one of three SQL-like embedded languages. Simple “SQL” over authority, “Java” program only, and a more Java-like hybrid embedded language. Furthermore, to transcribe the responses to the online quest and the participators' “task” solutions, the participators' eye movements were also recorded with an eye tracker. “Eye Tracker” or in this study call as “Eye-Trc” is the methodology of the study of software development that has developed nowadays and grants more in-depth info about how developers accomplish programming tasks. This Eye-Trc method is used as a data collection method in this study. Eye-Trc data was get by thirty-one participators (university background and Industrial Background) for different programming tasks. To analyze the impact of inter-group inconstant and professional experience and in-group “task” variables on the dependent variable Time in completion, this study used a mixed model ANOVA. The outcome of this study indicates that an important impact on productivity was not found, this is different from the initial research because of the language used. However, the same effect was found from the participators' expertise in programming activity indicating that more competent programmers were easy to full fill “polyglot programming tasks” more efficiently. In addition, it was raised that participators viewed the specimen code with the same proportion (time) for bringing “task” reckless of skills or language alternative provided. dominant-stage exploration management also remains mostly consistent over the experiences or language alternatives. Overall, it can be concluded that the programming stage of the linguist doesn’t have an important impact. The top-stage strategies that participators used came to be identical reckless of the language alternative presented to them. As a suggestion for future research, the impact of various characteristics of polyglot programming languages should be studied in depth for the conclusions reached to remain correct across various polyglot programming contexts.